SpaceFOM - A robust standard for enabling a-priori interoperability of HLA-based space systems simulations. Issue 6 (2nd November 2022) - Crues, Edwin Z.; Dexter, Dan; Falcone, Alberto; Garro, Alfredo; Möller, Björn
ABSTRACT: The development of modern space systems requires the collaboration among several national and international space organisations. Along with this complexity and diversity come progressively increasing challenges with managing the associated requirements, properties, emergent behaviours, and integration risks. Collaborative and distributed simulation is one technology being applied to address these challenges. A notable example of this is the well-established standard for distributed simulation, the IEEE 1516-2010 – High Level Architecture (HLA). To enable and ensure a-priori interoperability for complex space systems simulations and foster international collaboration, the Simulation Interoperability Standards Organization (SISO) formed a Product Development Group (PDG) to develop the Space Reference Federation Object Model (SpaceFOM). This article presents the SpaceFOM standard describing the principal design elements that compose it along with a set of design patterns introduced to deal with common issues in distributed simulation and to pursue extensibility, interoperability, and robustness.